The Effects of a Parenting Program on Maternal Well-Being: Evidence from a Randomized Controlled Trial - Georg Camehl; Kurt Hahlweg; C. Katharina Spieß (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper evaluates how the Triple P parenting program affects maternal well-being. We analyze data from a randomized controlled trial and a separate sample of mothers from a deprived neighborhood without a control group. For the latter, we generate a control group using SOEP survey data and evaluate the validity of this procedure. Overall, our results show a positive effect of Triple P on maternal well-being – with the largest effects appearing three years after treatment. Thus, we illustrate that maternal well-being is an additional channel through which parenting programs, as examples of early childhood interventions, benefit families.
Keywords: I31; I26; J13; C21; C26; 330; parenting program; family well-being; instrumental variables estimation; Triple P